Vigilance needed for endemic infections in pregnancy - Nature Research (16552612) (2019)
A hypertensive disorder of pregnancy, called preeclampsia, affects up to a tenth of all pregnant women globally and is thought to cause 40 to 60% of maternal deaths in developing countries. A complication of preeclampsia — called HELLP syndrome — causes haemolysis or destruction of red blood cells, elevated liver enzymes and a low platelet count. Now, a case report published in the Qatar Medical Journal is advising clinicians to consider HELLP syndrome as an alternative diagnosis for women living in areas endemic to malaria and scrub typhus. Malaria, a parasitic disease transmitted by mosquitos, affected 214 million people and killed 438,000 deaths in 2015 alone. Scrub typhus is a bacterial infection that affects millions annually in the Asia-Pacific region, 6 to 35% of whom are killed by the disease. Both infections typically cause fevers, but atypical presentations where fever is not reported are not uncommon, explains Habib Md Reazaul Karim of the North Eastern Indira Gandhi Regional Institute of Health and Medical Science in Shillong in eastern India. The study cites the case of a 26-year-old woman presented to hospital one day after childbirth with severe anaemia, shortness of breath, abdominal pain and drowsiness. She did not have a fever and had signs and symptoms that pointed to HELLP syndrome. And she tested negative for malaria. Treatment for HELLP helped her but only marginally. Since the patient came from a region where malaria and scrub typhus are widespread, she was then more thoroughly tested for both infections, returning positive results. When antimalarial treatment and antibiotics for scrub typhus were given, the patient’s laboratory tests improved over the following two days. “Our report gives a message that, even if fever is absent, malaria and scrub typhus should also be taken into account or ruled out in pregnant women presenting as HELLP syndrome,” says Karim. “Detecting and treating them early can save lives.” The researchers also cautioned against false negatives to malaria tests. Red blood cells infected with more mature stages of the malaria parasite get separated from the blood and destroyed in the spleen and placenta, leaving behind trace levels of the parasite in the peripheral blood that a standard peripheral blood smear may not detect. There is much room for further research. Scrub typhus during pregnancy is a particularly under-studied area that needs to be addressed and pregnancy outcomes in scrub typhus patients also need additional research, says Karim. Other Information Published in: QScience.com Highlights, Published by Nature Research for Hamad bin Khalifa University Press (HBKU Press) License: http://creativecommons.org/licenses/by/4.0